IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY (CSR) MELALUI PROGRAM PENGEMBANGAN MASYARAKAT (Studi Kasus pada Program CSR PT Unilever Indonesia, Tbk Melalui Program Pengembangan Petani Kedelai Hitam Yogyakarta) - Suryani, Ita (Communication, 2012)
The objective is to find out how the activities of Corporate Social Responsibility Program PT Unilever Indonesia Tbk In Black Soybean Farmers Development in Yogyakarta. The method used in this research that the case study method of research method that uses multiple sources of data that can be used to examine, describe and explain comprehensively the various aspects of individuals, groups, a program, organization or events systematically. The data obtained will be analyzed in a qualitative analysis is conducted to understand and assemble the data that has been collected and arranged systematically, and then draw conclusions. Research results show that with the implementation of Corporate Social Responsibility through community development programs, the organization can be viewed from two sides. First as a for-profit agencies, business organizations are viewed as economic institutions. But on the other hand, business organizations are also viewed as a social institution for bearing the burden of responsibility to society. The second role, namely the economic and social responsibilities that generate profits for the company and form a good image of concrete gains for both parties.